Assessment of heavy metals in agricultural soils and their source apportionment: a Turkish district survey - DARTAN, GÜLER (SPRINGER, 2015)
This study aimed at investigating the impact of industrialization on the quality of agricultural soils in the district of Bandirma, Turkey, in terms of soil heavy metal contamination. Many soil and phosphogypsum samples were analyzed, and enrichment factors (EFs) were calculated. The average concentration gradient of metals in the soil (mg/kg) was As<Se<Sb<Pb<Co<Cd<V<Cu<Ni<Zn<Cr<P<Mn<Na<K<Mg<Fe<Ca<Al. According to the Pearson cross-correlation results for the element pairs of Fe-Mg (0.635), Fe-Cu (0.863), Fe-Cd (0.545), Cu-Cd (0.630), Mn-Cr (0.698), Mn-Al (0.523), Cr-Mg (0.543), Al-P (0.508), Na-K (0.616), and C-Zn (0.703), the metal enrichments in the soil were found to be moderately high and significant. In the majority of soil samples, Ni, Cu, Co, Zn, Se, Pb, and Cr were moderately enriched whereas Sb and Cd were extremely highly enriched. A factor analysis (FA) was applied to the cross-correlations of the elements to identify their sources. Six significant factors were extracted with the help of FA, explaining 77.22 % of the total variance, and the elements loaded on these factors were interpreted. The evaluations of the factors showed that the study area has been exposed to heavy metal pollution from anthropogenic sources considering the high levels of Cr, Cd, Cu, P, V, Zn, Ni, Sb, and Pb in the soil and the higher EFs falling in the range of 2.54-372.87. Moreover, the soil concentrations of Mn, Mg, Co, Al, K, and Ca were also high, but they were of lithogenic in origin according to the FA.
Keywords: Heavy metals; Soil pollution; Phosphogypsum; Factor analysis; Enrichment factor; FERTILIZER INDUSTRY; TRACE-METALS; MULTIVARIATE; AREA; PHOSPHOGYPSUM; CONTAMINATION; URBAN